Analisis Strategi Perusahaan Multinasional Pt. Shinhan Indo Finance Dalam Mengembangkan Bisnis Di Indonesia - Dito Kurniawan (Universitas Tarumanagara, 2019)
Aim of this research is to analyze any strategies conducted by multinational company PT. Shinhan Indo Finance in expanding credit card business in Indonesia. This research use qualitative method whereas an interview was conducted to several departments in the company and to be compared to the theory initiated by Porter about Competitive Advantage of Nation and International Marketing Strategy. The interview has come with some results that Shinhan actually has good steps to expand the credit card business to new country but it has not been able to defeat competitors that has run the credit business since long time ago in Indonesia.